Neoechinulins: Molecular, cellular, and functional attributes as promising therapeutics against cancer and other human diseases - Sicon Mitra (Elsevier, 2022)
Neoechinulins are fungal and plant-derived chemicals extracted from Microsporum sp., Eurotium rubrum, Aspergillus sp., etc. Two analogues of neoechinulin, i.e., A and B, exerted extensive pharmacological properties described in this review. Neoechinulin is an indole alkaloid and has a double bond between C8/C9, which tends to contribute to its cytoprotective nature. Neoechinulin A exhibits protection to PC12 cells against nitrosative stress via increasing NAD(P)H reserve capacity and decreasing cellular GSH levels. It also confers protection via rescuing PC12 cells from rotenone-induced stress by lowering LDH leakage. This compound has great positive potential against neurodegenerative diseases by inhibiting SIN-1 induced cell death in neuronal cells. Together with these, neoechinulin A tends to inhibit Aβ42-induced microglial activation and confers protection against neuroinflammation. Alongside, it also inhibits cervical cancer cells by caspase-dependent apoptosis and via upregulation of apoptosis inducing genes like Bax, it suppresses LPS-induced inflammation in RAW264.7 macrophages and acts as an antidepressant. Whereas, another analogue, Neoechinulin B tends to interfere with the cellular mechanism thereby, inhibiting the entry of influenza A virus and it targets Liver X receptor (LXR) and decreases the infection rate of Hepatitis C. The present review describes the pharmaceutical properties of neoechinulins with notes on their molecular, cellular, and functional basis and their therapeutic properties.